Glycogen Synthase Kinase-3 is an Intermediate Modulator of Serotonin Neurotransmission - Li, Xiaohua; Polter, Abigail (Frontiers in Molecular Neuroscience, 2011)
Serotonin is a neurotransmitter with broad functions in brain development, neuronal activity, and behaviors; and serotonin is the prominent drug target in several major neuropsychiatric diseases. The multiple actions of serotonin are mediated by diverse serotonin receptor subtypes and associated signaling pathways. However, key signaling components that mediate specific function of serotonin neurotransmission have not been fully identified. This review will provide evidence from biochemical, pharmacological, and animal behavioral studies showing that serotonin regulates the activation states of brain glycogen synthase kinase-3 (GSK3) via type 1 and type 2 serotonin receptors. In return, GSK3 directly interacts with serotonin receptors in a highly selective manner, with a prominent effect on modulating serotonin 1B receptor activity. Therefore, GSK3 acts as an intermediate modulator in the serotonin neurotransmission system, and balanced GSK3 activity is essential for serotonin-regulated brain function and behaviors. Particularly important, several classes of serotonin-modulating drugs, such as antidepressants and atypical antipsychotics, regulate GSK3 toward inhibiting its activity in brain, which reinforces the importance of GSK3 as a potential therapeutic target in neuropsychiatric diseases associated with abnormal serotonin function.